Transformasi Perayaan Tabut Bengkulu : dari Ritual Keagamaan menjadi Agenda Tahunan Tahun 1998-2022 - Bintang, Kharisma; Salam, Abdul (Jurnal Kronologi, 2025)
This study examines the transformation of the Tabut Festival in Bengkulu from a sacred religious ritual into a publicly celebrated annual cultural agenda between 1998 and 2022. The transformation involves not only changes in form and implementation but also shifts in meaning, social function, and the actors involved. Utilizing historical research methods including heuristics, source criticism, interpretation, and historiography this study finds that internal factors such as modernization within the traditional custodian community, and external influences like government initiatives (e.g., the Visit Indonesia Year program) and the growth of cultural tourism, have contributed to the evolution of Tabot. While commercialization has become increasingly prominent, sacred elements are still preserved within the core rituals. The findings affirm that religious traditions can adapt to modern contexts and become instruments of local cultural identity without entirely losing their historical roots and spiritual significance.